Esophageal Variceal Ligation Monotherapy versus Combined Ligation and Sclerotherapy for the Treatment of Esophageal Varices. (30th March 2021) - Wang, Jianbo; Chen, Shenghui; Naga, Yehia M.; Liu, Junwei; Dai, Mugen; Yang, Shangwen; Wang, Liangjing; Ye, Bin
Abstract : Currently, endoscopic variceal ligation (EVL) monotherapy is the standard therapy for managing esophageal variceal hemorrhage. Patients generally need several sessions of endoscopy to achieve optimal variceal ablation, and the varices can recur afterward. Endoscopic injection sclerotherapy (EIS) is an older technique, associated with certain complications. This study aimed to evaluate the clinical efficacy of EVL alone versus combined EVL and EIS in the treatment of esophageal varices. This retrospective study included 84 patients, of which 40 patients were treated with EVL monotherapy and 44 patients were treated with combined EVL + EIS. The main outcomes were rebleeding rates, recurrence at six months, number of treatment sessions, length of hospital stay, cost of hospitalization, and procedural complications. At six months, the rebleeding rate and recurrence were significantly lower in the EVL + EIS group compared to the EVL group (2.3% versus 15.0%; and 9.1% versus 27.5%, respectively). The number of treatment sessions, length of hospital stay, and cost of hospitalization were significantly lower in the EVL + EIS group compared to those in the EVL group (2.3 ± 0.6 versus 3.2 ± 0.8 times; 14.5 ± 3.4 versus 23.5 ± 5.9 days; and 23918.6 ± 4220.4 versus 26165.2 ± 4765.1 renminbi, respectively). Chest pain was significantly lower in the EVL + EIS group compared to that in the EVL group (15.9% versus 45.0%). There were no statistically significant differences in the presence of fever or esophageal stricture in both groups. In conclusion, combined EVL + EIS showed less rebleeding rates and recurrence at six months and less chest pain and was more cost effective compared to EVL alone in the treatment of gastroesophageal varices.